ANALISIS KESALAHAN PEMAHAMAN KONSEP PADA MATERI PERKALIAN BERSUSUN SDN 35 KOTA SORONG: ANALYSIS OF MISUNDERSTANDING OF CONCEPTS IN COMPOSITE MULTIPLICATION MATERIAL AT SDN 35 KOTA SORONG - Kalauw, Sitra; Sundari; Ahmad, Rizky Ekawaty; Mardiah, Ainun (KAMBIK: Journal of Mathematics Education, 2024)
This study aims to understand and describe in depth the conceptual understanding errors in the material of stacked multiplication experienced by class 4C students of SDN 35 Sorong City. The study used a qualitative descriptive method that was carried out naturally in a natural situation without intervention. The subjects of the study were 25 class 4C students, with data collected through tests, interviews, and documentation. The test consisted of five stacked multiplication problems to identify the types of student errors, while the interviews aimed to dig deeper into students' understanding of the material being taught. The results of the study showed that student errors were divided into two types, namely conceptual errors and procedural errors. Conceptual errors mainly occur in long stacked multiplication, where students place numbers and lines incorrectly in the process of working, even though the final result is correct. Meanwhile, procedural errors arise because students do not follow the correct steps in solving long-stacked multiplication. The data analysis found that 60% of students made conceptual errors, while the other 40% made procedural errors. These findings indicate that errors in understanding compound multiplication material are caused by weak mastery of basic concepts, errors in solving steps, and ineffective teaching methods. To overcome this problem, it is necessary to strengthen basic concepts, structured exercises, and more interactive teaching approaches so that students can understand the steps for solving compound multiplication better. This study provides recommendations for teachers to develop more effective learning strategies to improve students' understanding of compound multiplication.